Extended release huperzine for the treatment of idiopathic epilepsy in dogs – a Case Report - Grant, Kylie L.; Long, Sam N. (Frontiers in Veterinary Science, 2025)
Huperzine is a naturally occurring alkaloid derived from the Chinese clubmoss Huperzia serrata. It is a potent acetylcholinesterase inhibitor, among other properties, and has demonstrated protection against induced seizures in a mouse model of Dravet’s syndrome as well as nerve-agent induced seizures and is being explored as a novel anticonvulsant in a human clinical trial for focal impaired awareness seizures. It is also being explored as a treatment for Alzheimer’s, via neuroprotective effects and an ability to ameliorate neuroinflammation. Here we present a case series of 6 dogs with idiopathic epilepsy treated with huperzine to investigate this potential novel anticonvulsant. Despite a 50% drop out rate over the course of the study due to various causes including unexplained death, humane euthanasia and systemic disease, huperzine was generally well tolerated and showed some positive effects on demeanor. This study highlights the need for more research to investigate its efficacy as a novel antiepileptic medication in dogs.